Some Recent Developments in the Valuation and Design of a New Deep Witwatersrand Gold Mine (The Australasian Institute of Mining and Metallurgy, 1986)
An enormous capital outlay is required to bring a new deep level (¦ 4 000 m deep) Witwatersrand gold mine into production. In addition, future mining methods must cater for rapidly rising working costs of which labour costs make up the largest portion. South African mining engineers are therefore being forced to challenge accepted design and valuation principles when planning these high risk ventures. New mining methods must be sought to satisfy the ever increasing need for productivity improvement. The technological problems posed by such changes cover a wide range of disciplines. Aspects of shaft design and configuration, besides being examined in the light of productivity, must also consider the rock mechanics implications at depth. Mining methods must anticipate and prepare for extremely hostile conditions due to seis- micity and virgin rock temperatures.